Pengembangan Sistem Arsip Digital dalam Upaya Peningkatan Pelayanan dan Administrasi Desa Muara Pulutan - Gunaidi, Aang; Yoanda, Sely; Rusmiatiningsih, Rusmiatiningsih (LIBTECH: LIBRARY AND INFORMATION SCIENCE JOURNAL, 2024)
The existence of village archives is very important in the sustainability process of a village. Village archives are created during the process of activities carried out by the village government. Archive management in Muara Pulutan Village is still done manually so the time required to retrieve information is not effective and efficient. The aim of this research is to develop an arterial system (integrated archives) for archive management in Muara Pulutan Village. This research uses a prototyping model which consists of communication stages, quick plan, modeling quick design, construction of prototype, deployment delivery and feedback. The research results show that the development of the arterial system (integrated archive) with a prototyping model was developed in accordance with the communication and quick plan. The quick plan stage is depicted in the form of a use case diagram which consists of adding archives, searching archives, master data, borrowing archives, reporting and access rights. Prototyping is given to stakeholders for consideration in ensuring and determining what functions are used. The next stage is the stage of deployment, delivery, and feedback which results in showing that all the main functions of the system are running according to user needs. The conclusion of this research is that the existence of a digital archive system in archival management in Muara Pulutan Village can facilitate the retrieval of required archive information, thereby improving the services provided by the village so that they can run effectively and efficiently.Keywords: village archives, digital archives, development system, prototyping